Specification for safety of household and similar electrical appliances. Particular requirements. Specification for safety of household and similar electrical appliances. Particular requirements. Commercial electric multi-purpose cooking pans Part 202-202.39, (28th September 1990) - British Standards Institution,
No abstract available